Dynamic protective potential of Couroupitaguianensis Aubl. against reactive free radicals: An approach of simulated in vitro model - Kavitha D; Madhumitha M
Oxygen is a prominent element in the well-being of humans, but also responsible for causing tissue damage. The oxygen molecule gets reduced to form a highly reactive oxygen species due to various metabolic events happening in the host. The generated free radicals could react with other biomolecules like protein, lipid, carbohydrate and nucleic acid to impart severediseases and disorders. Antioxidants could effectively block the oxidation process by neutralizing the produced free radicals. Hence, the present study aims to validate the potent antioxidant activities of Couroupita guianensis Aubl. using goat liver slices that could serve as an in vivo simulated in vitro model. The methanolic extract and the alkaloid fraction of both leaves and flowers of C. guianensis Aubl. were prepared and their enzymatic and non-enzymatic antioxidant activities were evaluated. Hydrogen peroxide was used as a standard free radical throughout the experiments in all the treatment groups. The results have envisaged that the plant has enormous antioxidant activities in oxidatively stressed goat liver slices to combat various oxidative stress-related diseases and disorders. Conclusively, the in vitro model system to explore the antioxidant profiles will eventually mitigate the sacrifice of animals by exactly mimicking the in vivo conditions for research endeavors